2021
DOI: 10.1002/advs.202103090
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Fueled Polymer Film Capable of Directional Crawling, Friction‐Controlled Climbing, and Self‐Sustained Motion on a Human Hair

Abstract: Recent efforts in stimuli-responsive soft materials have enabled wirelessly controlled actuation with increasing degrees of freedom, yielding miniature robots capable of various locomotion in open environments such as on a plane or inside fluids. However, grand challenges remain in harnessing photomechanical deformation to induce locomotion and control of friction during the movement, especially for robotic actuations within constrained spaces. Here, the authors report a centimeter-long polymer strip made of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…13a . Cheng et al 261 demonstrated the light-controlled friction and locomotion of a centimeter-long polymer stripe under a constrained condition of a human hair, Fig. 13b .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…13a . Cheng et al 261 demonstrated the light-controlled friction and locomotion of a centimeter-long polymer stripe under a constrained condition of a human hair, Fig. 13b .…”
Section: Applicationsmentioning
confidence: 99%
“… 251 , with permission of Wiley-VCH. b Light-activated LC actuators climbing on human hairs 261 . Reproduced from ref.…”
Section: Applicationsmentioning
confidence: 99%
“…Crawling is one of the simplest modes of movement. Photothermal-driven LCE soft robots can crawl in complex and extreme environments because of the softness of the body [ 7 , 27 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. In addition, the robots can be made smaller because they do not need to carry a power source like traditional robots, as light can provide energy remotely.…”
Section: Applicationmentioning
confidence: 99%
“…The addition of CNT not only contributes to photothermal conversion, but also enhances the mechanical properties of materials, which provides support for expanding the potential application scenarios for photothermal-driven LCEs. Cheng et al [ 89 ] reported a light-driven LCE film that could crawl along a hair ( Figure 10 d). The micro-structure of the hair’s surface provided different friction coefficients in different directions, allowing the soft robot to move along the hair in a single direction when stimulated by a manual scanning light beam.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation